Factors Affecting the Incidence of Chronic Lack Energy (SEZ) in Pregnant Women at the Tanjung Unggat Health Center, Tanjung Pinang City, Kepri Province in 2023 - Nasution, Ramadhani Syafitri; Susanti, Ika; Nasution, Zuraidah (Universitas Ibn Khaldun Bogor, 2024)
Chronic energy deficiency (CED) in pregnant women is a condition of insufficient protein and energy intake which can cause health problems for the mother and fetus. This study aims to determine the factors that influence the occurrence of CED in pregnant women. An analytical survey method with a cross-sectional approach was used by collecting primary data through questionnaires and secondary data from Community Health Center reports. The research was conducted at the Tanjung Unggat Community Health Center, Tanjungpinang City in December 2023 with a sample of 51 pregnant women selected using the Total Sampling method. Data analysis used univariate, bivariate (chi-square test), and multivariate (logistic regression) analysis. The results of the analysis show that maternal age, education, employment, parity, knowledge, Body Mass Index (BMI), and hemoglobin (Hb) levels have a significant relationship with the occurrence of CED. The Hb variable has the greatest influence on KEK with an Exp (B) value of 15,098. This study concludes that there is no effect of age and education on CED, while employment, parity, knowledge, BMI, and Hb are related to the incidence of CED in pregnant women. It is recommended that health workers promote and prevent pregnant women by recommending regular Antenatal Care (ANC) visits to health workers to detect health conditions early.